Zinc mediates the action of androgen in acting as a downstream effector of luteinizing hormone on oocyte maturation in zebrafish. Issue 2 (6th November 2018) - Li, Jianzhen; Huang, Duo; Sun, Xiao; Li, Xuehui; Cheng, Christopher H K
Abstract: The role of androgenic steroids on ovarian development has attracted much attention in recent years, but the molecular mechanism is still largely unknown. In this study, using zebrafish as a model, we found that the trace metal zinc mediates the action of androgen on oocyte maturation. The ovarian and serum testosterone is transiently stimulated by LH during oocyte maturation. Testosterone could mimic the action of LH on oocyte maturation, and its action appears to be independent of the classical nuclear androgen receptor. Consistent with a recent finding that a zinc transporter (Zip9) has been suggested as a novel androgen receptor, we found the labile zinc concentration could be induced by testosterone in the ovarian follicular cells, and zinc could mimic the action of testosterone on oocyte maturation and signaling. Moreover, the action of testosterone on oocyte maturation could be abolished by the chelation of zinc. Thus, the evidence supports the notion that zinc could mediate the action of androgen on oocyte maturation in zebrafish. This finding would shed light on understanding the role of androgen in ovary development and the molecular mechanism of oocyte maturation in fish. Abstract : Zinc could mediate the action of androgen on oocyte maturation in zebrafish.